A broadband tunable asymmetric transmission structure design. (1st June 2022) - Wang, Wei; Xuan, Chengming; Qi, Wuchao; Yang, Zhe; Xu, Weikai
Abstract: In this paper, we design a tunable asymmetric transmission structure consisting of a one-dimensional phononic crystal metastructure and a simple mass oscillator metasurface. By reasonably adjusting the width of the supercell in the metasurface, transmission control of the flexural wave can be achieved. According to the generalized Snell's law, anomalous refraction occurs when the flexural wave is obliquely incident, while total reflection will occur when the flexural wave is vertically incident. The one-dimensional phononic crystal metastructure can be used to deflect the perpendicularly incident flexural wave. In combination with the metasurface, the asymmetric transmission of flexural waves over a quite wide frequency range can be achieved. The designed asymmetric transmission structure has both tunability and broadband capability. Adjusting the distance of the mass oscillators in the metastructure and the phase distribution of the metasurface can realize the modulation of refraction angles, while increasing or decreasing the number of mass oscillators can further expand the operating frequency domain of the tunable asymmetric transmission structure. Numerical results show that the proposed structure can achieve asymmetric transmission of flexural waves in the frequency domain of 13–25 kHz or even wider.